2015
DOI: 10.1093/aobpla/plu088
|View full text |Cite
|
Sign up to set email alerts
|

Trichomes related to an unusual method of water retention and protection of the stem apex in an arid zone perennial species

Abstract: Plant adaptation strategies to harsh environments are among the most interesting subjects in plant biology. Several studies have investigated the role trichomes play in protecting plant organs in these conditions. In this work we report an unusual way of protecting the stem apex of Lychnophora diamantinana. The terminal cell of its non-glandular trichomes undergoes partial degradation of the cell wall, producing a highly hydrated, hyaline material that protects the stem apex against desiccation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Numerous studies have shown plant trichomes are involved in water protection, absorbing UV radiation, and attracting pollinators by releasing specific chemicals (Skaltsa et al, 1994 ; Moraes et al, 1998 ; Paré and Tumlinson, 1999 ; Benz and Martin, 2006 ; Lusa et al, 2014 ). However, the most notable function of plant trichomes is their role in plant defense.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown plant trichomes are involved in water protection, absorbing UV radiation, and attracting pollinators by releasing specific chemicals (Skaltsa et al, 1994 ; Moraes et al, 1998 ; Paré and Tumlinson, 1999 ; Benz and Martin, 2006 ; Lusa et al, 2014 ). However, the most notable function of plant trichomes is their role in plant defense.…”
Section: Introductionmentioning
confidence: 99%
“…Lychnophorinae are one of the most representative subtribes of Vernonieae in Brazil (Keeley & Robinson, ), comprising 18 genera and 104 species including shrubs, subshrubs, trees and treelets, which are nearly all restricted to the Cerrado Domain, occurring predominantly in campos rupestres (Loeuille et al ., ) and exhibiting morphological and anatomical adaptations to these arid zones (Lusa et al ., , ). Findings of recent phylogenetic analysis for Lychnophorinae based on molecular and morphological data show that the subtribe is monophyletic (Loeuille, Keeley & Pirani, ).…”
Section: Introductionmentioning
confidence: 99%
“…They produce hydrophilic substances that help to retain water, thereby preventing drying out and promoting the growth of young organs. This hyaline material contained mainly carbohydrates derived from the partial degradation of the trichome cell wall (Lusa et al 2015). The secretion of colleters on the surface of buds and floral elements protects against water loss as well (Mayer et al 2013).…”
Section: Micromorphologymentioning
confidence: 99%
“…The secretion of colleters on the surface of buds and floral elements protects against water loss as well (Mayer et al 2013). Some glandular trichomes provide food for pollinators (Pansarin and Maciel 2017), while others secrete terpenoids, phenolic compounds, and insect-repellent proteins (Lusa et al 2015). Accumulation of e.g.…”
Section: Micromorphologymentioning
confidence: 99%